Understanding human evolutionary history: a meeting report of the Swedish Royal Academy of Sciences symposium of modern human genetic variation - Akey, Joshua M (BioMed Central, 2012)
A report on the Swedish Royal Academy of Sciences Symposium on Modern Human Genetic Variation. Stockholm, Sweden. January 19-20, 2012.